2023
DOI: 10.3389/fsurg.2023.1099457
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic negative pressure therapy for duodenal leaks

Abstract: Background and study aimEndoscopic negative pressure therapy (ENPT) is well established in the treatment of perforations of various etiologies in the upper and lower gastrointestinal tract. For duodenal perforations exist only case reports and series. Different indications are possible for ENPT in duodenal position: primary therapy for leaks, preemptive therapy after surgery for example, after ulcer suturing or resection with anastomoses, or as second line therapy in cases of recurrent anastomotic insufficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The OFD can be easily forwarded into the stomach and then guided through the pylorus with an endoscopic forceps, like a standard enteral feeding tube. The feasibility and efficacy of this treatment have been demonstrated in small case series for various duodenal defects, including perforated duodenal diverticula, iatrogenic perforations after ERCP or endoscopic mucosal resection, and anastomotic leaks, and it has been a game changer for the minimally invasive treatment of these challenging cases [25,[31][32][33][34]. A recent experimental study also showed the high drainage capacity of the OFD, a feature particularly important in the duodenum, where the presence of bile and pancreatic secretions can have a negative effect on tissue healing [35].…”
Section: Clinical Applications and Outcomes Of Ofdmentioning
confidence: 99%
“…The OFD can be easily forwarded into the stomach and then guided through the pylorus with an endoscopic forceps, like a standard enteral feeding tube. The feasibility and efficacy of this treatment have been demonstrated in small case series for various duodenal defects, including perforated duodenal diverticula, iatrogenic perforations after ERCP or endoscopic mucosal resection, and anastomotic leaks, and it has been a game changer for the minimally invasive treatment of these challenging cases [25,[31][32][33][34]. A recent experimental study also showed the high drainage capacity of the OFD, a feature particularly important in the duodenum, where the presence of bile and pancreatic secretions can have a negative effect on tissue healing [35].…”
Section: Clinical Applications and Outcomes Of Ofdmentioning
confidence: 99%